Percutaneous minimal‐access fetoscopic surgery for spina bifida aperta. Part II: maternal management and outcome. (November 2014) - Degenhardt, J.; Schürg, R.; Winarno, A.; Oehmke, F.; Khaleeva, A.; Kawecki, A.; Enzensberger, C.; Tinneberg, H.‐R.; Faas, D.; Ehrhardt, H.; Axt‐Fliedner, R.; Kohl, T.
ABSTRACT Objective To assess maternal morbidity and outcome in women undergoing minimal‐access fetoscopic surgery for spina bifida aperta. Methods This was a retrospective study of 51 women undergoing minimal‐access fetoscopic surgery to improve postnatal neurological outcome of spina bifida aperta, at a mean gestational age of 24 weeks, at our center between July 2010 and June 2013. We analyzed various perioperative complications of surgery, namely: maternal and fetal death, need for maternal blood transfusion, placental abruption, pulmonary edema, spontaneous labor, oligohydramnios, chorioamnionitis, chorioamniotic membrane separation, duration of hospitalization, amniotic fluid leakage, gestational age at delivery and status of hysterotomy site. Results In none of the 51 women was there maternal demise, spontaneous labor, placental abruption or a need for maternal blood transfusion in the perioperative period. Chorioamniotic membrane separation occurred in one patient, mild pulmonary edema occurred in one and oligohydramnios occurred in seven. All fetuses survived surgery, but there was one very early preterm delivery 1 week after the procedure and this neonate died immediately, from early postoperative chorioamnionitis. Amniotic fluid leakage occurred in 43 patients, at a mean gestational age of 29.7 (range, 22.6–37.3) weeks; two of these patients developed chorioamnionitis. Duration of maternal hospitalization after surgery was 7.2 (range, 4–12) days. Mean gestational age at delivery was 33 (range, 24.6–38.1) weeks. All abdominal and uterine trocar insertion sites healed well. Conclusion Minimal‐access fetoscopic surgery for spina bifida aperta is apparently safe for most maternal patients. Despite the common occurrence of amniotic leakage, the majority of women deliver beyond 32 weeks of gestation. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.